Língua materna: a morada do sujeito - Reis, Cristhiane Bonasorte dos (2022)
The issue of the mother tongue is the object of reflection and study in this thesis. The presente work approaches the problem of the mother tongue firstly in the encounter with the essay De Vulgari Eloquentia, written by Dante Alighieri, receives an argumentative basis in the text O amor da língua, by Jean-Claude Milner (1987), and discusses the notion of moyher tongue in the field of Language Acquisition from Interactionism and the Language Clinic. Finally, the literature already developed on the problem of the mother tongue is reviewed